Demographic factors and marital satisfaction among Iranian married students in Malaysia - Ahangar, Katayoon; Juhari, Rumaya; Yaacob, Siti Nor; Abu Talib, Mansor (Leena & Luna International (Pvt) Limited, 2016)
Marriage is a special relationship between two people which its quality plays an important role in one’s life. Marital satisfaction is a personal feeling about and strongly related to health and happiness of marriage. This study aims to examine the relationships between demographic factors and marital satisfaction. Subjects for this study were 387 Iranian married students. The instrument used was ENRICH Marital Satisfaction Scale to measure marital satisfaction. Results indicated that age, length of marriage, arranged marriage and educational level have significant relationship with marital satisfaction, however, length of stay in Malaysia, income and gender do not have any significant relationship with marital satisfaction. This study recommends that marriage counseling, with an emphasis on promoting awareness in marital happiness and satisfaction, would be helpful in addressing marital conflicts among international married students.